Merekonstruksi Ekonomi Pembangunan dalam Perspektif Islam: Menjawab Kegagalan Kapitalisme terhadap Kesejahteraan Sejati - Wahyu Hardi Santika; Miftahus Surur (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Capitalism is often considered to be contrary to Islamic values because it is believed to cause social inequality, exploitation, and injustice in the distribution of wealth. This view arises because the capitalist system emphasizes individual ownership and unlimited capital accumulation, while Islam emphasizes a balance between individual rights and social interests. In the context of Indonesia, where the majority of the population is Muslim, there have been various efforts to harmonize modern capitalism and Islamic economic principles. This study uses a descriptive qualitative approach with a literature review method to analyze how Islamic values can be applied in a capitalist economic system. This study focuses on the application of sharia principles such as the prohibition of usury, the obligation of zakat, the principle of justice, and social responsibility in economic activities. The results of the study show that the application of these Islamic values can foster business ethics, improve economic equality, and encourage inclusive and sustainable economic growth. The integration between capitalism and Islamic teachings also shows that Islam does not absolutely reject capitalism, but rather directs that the system be run with moral, spiritual, and mutual benefit values. Thus, the application of Sharia principles can make capitalism more humane and oriented towards social welfare, not just material gain. These findings form the basis for the development of a just economy that is in line with universal Islamic values.